2011
DOI: 10.2478/v10078-011-0049-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hand Dimensions, Hand Shape and Some Anthropometric Characteristics on Handgrip Strength in Male Grip Athletes and Non-Athletes

Abstract: It has been suggested that athletes with longer fingers and larger hand surfaces enjoy stronger grip power. Therefore, some researchers have examined a number of factors and anthropometric variables that explain this issue. To our knowledge, the data is scarce. Thus, the aim of this study was to investigate the effect of hand dimensions, hand shape and some anthropometric characteristics on handgrip strength in male grip athletes and non-athletes. 80 subjects aged between 19 and 29 participated in this study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 18 publications
5
75
3
5
Order By: Relevance
“…Similar result with our finding, i.e., HGS is positively correlated with is percenatge of lean body mass is shown by Fallahi and Jadidian (r = 0.536). [29] Dissimilar result with our finding, i.e., HGS is negatively correlated with is percentage of lean body mass is shown by author Koley and Yadav (for right-hand r = −0.400 and for light hand r = −0.372). [25] More lean body mass will lead to more muscle area.…”
Section: Discussioncontrasting
confidence: 47%
“…Similar result with our finding, i.e., HGS is positively correlated with is percenatge of lean body mass is shown by Fallahi and Jadidian (r = 0.536). [29] Dissimilar result with our finding, i.e., HGS is negatively correlated with is percentage of lean body mass is shown by author Koley and Yadav (for right-hand r = −0.400 and for light hand r = −0.372). [25] More lean body mass will lead to more muscle area.…”
Section: Discussioncontrasting
confidence: 47%
“…8 Several factors were found to affect handgrip strength such as age, gender, muscle mass, body mass index, and hand dimensions. 9 Proper handgrip strength is essential for carrying precise hand functions such as gripping and pulling. It is considered a crucial factor in maximizing performance and control of many daily activities and sporting.…”
Section: Introductionmentioning
confidence: 99%
“…In sports involving grasping an object such as basketball and handball, players with bigger hands and longer fingers have better accuracy of the shot [16]. In other grip sports like rock climbing, wrestling or judo, hand Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…This may work more efficiently when the fingers and hand surface parameters are longer and when the fingers are stronger (which likely yields better handgrip strength). Recently, Fallahi and Jadidian [16] showed that handgrip strength and some of the hand dimensions may be different in athletes who have handgrip movements with an object or opponent in comparison to non-athletes. Also, there was a significant positive correlation between handgrip strength and most of the hand dimensions in grip athletes.…”
Section: Introductionmentioning
confidence: 99%